2019
DOI: 10.20517/2394-4722.2019.32
|View full text |Cite
|
Sign up to set email alerts
|

Novel immunotherapeutic approaches in head and neck cancer

Abstract: Unresectable recurrent or metastatic head and neck cancer is an incurable disease with survival of approximately 12 months. Head and neck tumors exhibit numerous derangements in the tumor microenvironment that aid in immune evasion and may serve as targets for future therapies. Pembrolizumab is now approved as a first line therapy. Despite the promise of currently approved immunotherapies there continues to be low response rates and additional strategies are needed. Here, alterations in the immune microenviron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…There are several common biomarkers of immune-checkpoint inhibitor (ICI) under evaluation, including tumor-infiltrating lymphocytes (TIL), interferon gamma (IFN- ), and tumor mutational burden (TMB) [ 23 ]. The other ICI, anti-LAG-3 (pelatlimab), is currently being evaluated in phase I/IIA [ 50 ] (ClinicalTrials.gov Identifier: NCT01968109) and II-IVA [ 94 ] (NCT04080804) studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are several common biomarkers of immune-checkpoint inhibitor (ICI) under evaluation, including tumor-infiltrating lymphocytes (TIL), interferon gamma (IFN- ), and tumor mutational burden (TMB) [ 23 ]. The other ICI, anti-LAG-3 (pelatlimab), is currently being evaluated in phase I/IIA [ 50 ] (ClinicalTrials.gov Identifier: NCT01968109) and II-IVA [ 94 ] (NCT04080804) studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in diagnostics, treatment, and close follow-up by serum Tumor Markers, the 5-year progression-free survival (PFS) or survival rates for recurrent/metastatic (R/M) disease -have not significantly changed over the past years [3][4][5]24]. Recent treatments include NIVOLUMAB -B and PEMBROLIZUMAB -C, in addition to formerly used Methotrexate, Docetaxel and Cetuximab [25]. In a randomized, open-label, phase 3 study at 97 medical centers in 20 countries, they demonstrated a prolongation of overall survival (OS) and favorable safety of Pembrolizumab in patients with recurrent or metastatic HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several common biomarkers of ICI under evaluation, which include tumor-infiltrating lymphocytes (TIL), interferon gamma (IFN-γ), and tumor mutational burden (TMB) [23]. The other ICI, anti-LAG-3 (pelatlimab), is currently evaluated under the phase I/IIA [32](ClinicalTrials.gov Identifier: NCT01968109) and II-IVA [64](ClinicalTrials.gov Identifier: NCT04080804) studies.…”
Section: Discussionmentioning
confidence: 99%